New developments in the treatment of chemotherapy-induced neutropenia: focus on balugrastim - Ghidini M; Hahne JC; Trevisani F; Panni S; Ratti M; Toppo L; Tomasello G (Therapeutics and Clinical Risk Management, 2016)
Michele Ghidini,1 Jens Claus Hahne,2 Francesco Trevisani,3 Stefano Panni,1 Margherita Ratti,1 Laura Toppo,1 Gianluca Tomasello1 1Medical Department, Division of Oncology, ASST di Cremona, Ospedale di Cremona, Cremona, Italy; 2Division of Molecular Pathology, The Institute of Cancer Research, London and Sutton, UK; 3Department of Urology, Unit of Urology/Division of Oncology, IRCCS Ospedale San Raffaele, URI, Milan, Italy Abstract: Neutropenia and febrile neutropenia are two major complications of chemotherapy. Dose reductions, delays in treatment administration, and the use of granulocyte colony-stimulating factors are equally recommended options to preserve absolute neutrophil count in case of chemotherapy regimens bringing a risk of febrile neutropenia of 20% or higher. Recombinant granulocyte colony-stimulating factors, such as filgrastim and lenograstim, have a short elimination half-life (t1/2) and need to be used daily, while others, like pegfilgrastim and lipegfilgrastim, are characterized by a long t1/2 requiring only a single administration per cycle. Balugrastim is a novel long-acting recombinant granulocyte colony-stimulating factor obtained by means of a genetic fusion between recombinant human serum albumin and granulocyte colony-stimulating factor. Albumin binding increases the molecular weight and determines a high plasmatic stability leading to a t1/2 of ~19 days. Balugrastim’s efficacy, safety, and tolerability have been assessed in four different clinical trials involving breast cancer patients treated with doxorubicin and docetaxel. Pegfilgrastim was chosen as a comparator. Balugrastim was noninferior to pegfilgrastim with regard to the reduction of mean duration of severe neutropenia during cycle 1. Moreover, both treatments were comparable in terms of efficacy and safety profile. Balugrastim was well tolerated, with the only related adverse event being mild to moderate bone pain. The aim of this review is to summarize the currently available literature data on balugrastim. Keywords: G-CSF, granulocyte colony-stimulating factors, albumin, febrile neutropenia, pegfilgrastim